Role of Multi parametric MRI in Differentiating Focal Liver Lesions: A Comparative Study with Contrast-Enhanced Ultrasound (The Review of Diabetic Studies, 2025)
Background: Focal liver lesions (FLLs) constitute one of the significant diagnostic conundrums in the realm of medical practice. Comprehensive approaches, as offered by the gamut of multi-parametric imaging using magnetic resonance imaging techniques such as the incorporation of diffusion-weighted imaging, diffusion tensor imaging, and magnetic resonance elastography, compare favorably with contrast-enhanced ultrasound approaches. This review collates the evidence regarding the differentiation of benign from malignant FLLs using the aforementioned diagnostic modalities.Objective: Evaluate the performance of multi parametric MRI modalities with contrast-enhanced ultrasound methods regarding their ability to identify focal liver lesions, with special reference to sensitivity and specificity.Methods: Data from recent comparative studies evaluating MRE, DWI, DTI, and parametric contrast-enhanced ultrasound were analyzed. Comparisons between diagnostic accuracy metrics such as sensitivity and specificity, ADC and FA values, and stiffness measurements across all modalities were performed.Results: MRE thus showed a sensitivity of 93.8-97.3% and a specificity of 89.9-90.9%, whereas the sensitivity of DWI alone ranged between 77.9-87.6%, while its specificity ranged from 51.5-83.4%. DTI likewise demonstrated significant differences in both ADC values-benign, 2.152 × 10⁻³ mm²/s vs. malignant, 1.212 × 10⁻³ mm²/s (p